Mediating effects of remuneration on earnings management and firm equity value - Premagowrie Sivanandan; Nor Shaipah Abdul Wahab (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study examines the potential mediating effects of executive remuneration on the relationship between prior-year earnings management and firm equity value. The occurrence of financial scandals in Malaysia has been associated with earnings management, which entails opportunistic manipulation of a firm’s earnings by managers. Managers who are driven by opportunism, engage in earnings management through the manipulation of discretionary accruals (known as accrual-based earnings management method (AEM)) or real activities (known as real earnings management method (REM)) to attain personal wealth maximisation. This is because when executive remuneration is linked to firm performance, managers are incentivised to manage earnings to boost firm performance with the aim to maximise their performance-based remuneration. Thus, through executive remuneration, earnings management may affect firm equity value. However, empirical evidence on the mediating effects of executive remuneration on earnings management and firm equity value is generally scarce. Therefore, using 601 non-financial firms listed on Bursa Malaysia’s Main Market from 2013 to 2017, this study finds significant mediation of executive remuneration on the relationship between both earnings management methods and firm equity value in a different manner. This implies that the mediating effects of executive remuneration lies on the methods of earnings management. This paper, thus, provides insights to financial reporting and corporate governance regulators, and key management personnel of Malaysian public listed firms on the importance of executive remuneration on equity valuation of earnings management. This paper also methodologically contributes to literature by establishing mediation model within the earnings management area.